2011
DOI: 10.1149/1.3565501
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thermo-Vacuum Systems in the Dye Sensitized Solar Cell

Abstract: Dye-Sensitized Solar Cell (DSSC) is currently under the developing progress in worldwide. Usually the laboratories adopt the method for absorbing dyes on film electrodes through placing the specimen sample in the dye for a lengthy soaking (12 hours). Consequently, the study employs the cooperation of thermo-vacuum system on the heating processes. We discovered from the experimental results that the best performance resulted from the heating process, which not only sped up the diffusion velocity of dye molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Sintering is a thermal treatment to form connection of small TiO2 particles into a solid structure. Furthermore, sintering formed a porous TiO2 films which have a large surface area [14] and removed organic compounds that is trapped in the pores of the TiO2. Sintering process was carried out at temperatures, ranging from 400 oC to 500 oC.…”
Section: Effect Of Sintering Methods On Dye Sensitized Solar Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Sintering is a thermal treatment to form connection of small TiO2 particles into a solid structure. Furthermore, sintering formed a porous TiO2 films which have a large surface area [14] and removed organic compounds that is trapped in the pores of the TiO2. Sintering process was carried out at temperatures, ranging from 400 oC to 500 oC.…”
Section: Effect Of Sintering Methods On Dye Sensitized Solar Cellmentioning
confidence: 99%
“…Soaking temperature affected the absorption of the dye on the TiO2 film. The result of Jheng et al's research showed that heating process would not only speed up the diffusion velocity of the dye solution being absorbed but also enhance conversion efficiency [14]. In addition, soaking of the working electrode in the dye solution at 40 -50 oC would open the pores of TiO2.…”
Section: Effect Of Soaking Methods On Dye Sensitized Solar Cellmentioning
confidence: 99%